'Active'ating thoughts about affect: elicitation of physical activity judgements in insufficiently active women. Issue 5 (4th May 2019) - Ruissen, Geralyn R.; Rhodes, Ryan E.; Beauchamp, Mark R.
Abstract: Objective: A growing body of evidence suggests that affective judgements are distinct from, and exert greater influence on, physical activity behaviours than instrumental judgements. Design: As part of a randomised controlled trial, 110 insufficiently active, female, university students were randomised to (a) an affective mental contrasting condition, (b) an instrumental mental contrasting condition, or (c) a 'standard' mental contrasting intervention (with no modifications). In the analyses concerning the trial's primary outcome, the affective mental contrasting condition was found to be more effective for increasing physical activity than the standard or instrumental conditions. The purpose of this study was to qualitatively examine the physical activity outcomes and obstacles elicited from participants as part of the three mental contrasting interventions within this trial. Results: 32 lower-order physical activity judgement themes, categorised within seven high-order themes, were derived through the use of the mental contrasting intervention. In addition to identifying several affective and instrumental outcomes and obstacles that have previously been recognised, participants in this study also highlighted contextualised responses that describe complicated relationships that exist between affective and instrumental judgements. Conclusions: This study provides fine-grained insight into cognitive processes derived from a novel intervention involving insufficiently active women.